The malaria parasite Plasmodium relictum in the endemic avifauna of eastern Cuba. Issue 6 (30th August 2017) - Soares, Letícia; Marra, Peter; Gray, Lindsey; Ricklefs, Robert E.
Abstract: Island populations are vulnerable to introduced pathogens, as evidenced by extinction or population decline of several endemic Hawaiian birds caused by the malaria parasite, Plasmodium relictum (order Haemosporida). We analyzed blood samples from 363 birds caught near Guantánamo Bay, Cuba, for the presence of haemosporidian infections. We characterized parasite lineages by determining nucleotide variation of the parasite's mitochondrial cyt b gene. Fifty‐nine individuals were infected, and we identified 7 lineages of haemosporidian parasites. Fifty individuals were infected by 6 Haemoproteus sp. lineages, including a newly characterized lineage of Haem. ( Parahaemoproteus ) sp. CUH01. Nine individuals carried the P. relictum lineage GRW4, including 5 endemic Cuban Grassquits ( Tiaris canorus ) and 1 migratory Cape May Warbler ( Setophaga tigrina ). A sequence of the merozoite surface protein gene from one Cuban Grassquit infected with GRW4 matched that of the Hawaiian haplotype Pr9. Our results indicate that resident and migratory Cuban birds are infected with a malaria lineage that has severely affected populations of several endemic Hawaiian birds. We suggest GRW4 may be associated with the lack of several bird species on Cuba that are ubiquitous elsewhere in the West Indies. From the standpoint of avian conservation in the Caribbean Basin, it will be important to determine the distribution of haemosporidian parasites, especially P. relictum GRW4, in Cuba as well as the pathogenicity of this lineage in species that occur and are absent from Cuba.